Mapping and Functional Characterization of Stigma Exposed 1, a DUF1005 Gene Controlling Petal and Stigma Cells in Mungbean (Vigna radiata) - Lin, Yun; Laosatit, Kularb; Chen, Jingbin; Yuan, Xingxing; Wu, Ranran; Amkul, Kitiya; Chen, Xin; Somta, Prakit (Frontiers in Plant Science, 2020)
Flowers with exposed stigma increase the outcrossing rate and are useful in developing improved hybrid crop cultivars. This exposure results mainly from the cellular morphology of the petal and pistil, but what affects the formation of the petal and pistil in the late developmental stages is less understood. Here, we characterized a novel floral mutant in mungbean (Vigna radiata), stigma exposed 1 (se1), which displays irregular petals and pistils. Floral organ initiation in the se1 mutant was normal, but petal and pistil growth malfunctioned during late development. A histological analysis revealed that the se1 mutant had wrinkled petals with knotted structures and elongated styles. The cellular morphology of the epidermal layers of the se1 petals was deformed, while the cell lengths in the styles increased. A genetic analysis indicated that the se1 phenotype is controlled by a single recessive gene, and it was mapped to chromosome 11. A sequence analysis suggested that a DUF1005-encoding gene, LOC106777793, is the gene controlling the se1 phenotype. The se1 mutant possessed a single nucleotide polymorphism that resulted in an amino acid change in VrDUF1005. Overexpression of VrDUF1005 in Arabidopsis resulted in rolling leaves and reduced floral size. Consequently, we proposed that VrSE1 functions to modulate cell division in petals and cell expansion in styles during the late developmental stages in mungbean. The se1 mutant is a new genetic resource for mung bean hybrid breeding.